2007
DOI: 10.1103/physrevb.75.054424
|View full text |Cite
|
Sign up to set email alerts
|

Spatial inhomogeneity of magnetic moments in the cobalt oxide spinelCo3O4

Abstract: The antiferromagnetic ͑AF͒ nature of the normal spinel Co 3 O 4 with Néel temperature ͑T N ͒ =30 K was investigated by means of positive muon spin rotation and relaxation ͑ + SR͒ techniques using a polycrystalline sample. Clear muon spin precession signals due to a quasistatic long-range AF order were found in the zero-field + SR spectra below T N. The spectra consist of two oscillating signals with frequencies at T → 0 K of 80 and 60 MHz, respectively, indicating an incommensurate ͑IC͒ AF order in Co 3 O 4. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 41 publications
5
43
3
Order By: Relevance
“…The best fits presented in Fig. 4 Our findings give a natural explanation of the SR results 8 on Co 3 O 4 as due to spin-liquid physics rather than incommensurate magnetic order. Also, based on the position of CoAl 2 O 4 in the J 2 / J 1 phase diagram, we suggest that even in an ideal sample, with no inversion or other perturbation, the ground state would be a collinear AFM, though one might need very low temperatures to reach it.…”
Section: Modelingsupporting
confidence: 54%
See 1 more Smart Citation
“…The best fits presented in Fig. 4 Our findings give a natural explanation of the SR results 8 on Co 3 O 4 as due to spin-liquid physics rather than incommensurate magnetic order. Also, based on the position of CoAl 2 O 4 in the J 2 / J 1 phase diagram, we suggest that even in an ideal sample, with no inversion or other perturbation, the ground state would be a collinear AFM, though one might need very low temperatures to reach it.…”
Section: Modelingsupporting
confidence: 54%
“…Existing experiments on Co-Al oxide spinels do not provide a clear picture. An early neutron-diffraction study 7 on Co 3 O 4 showed that the magnetic moments of the Co 2+ ions located at the tetrahedral sites form a simple collinear AFM below the Neel temperature T N = 40 K. This picture has been questioned by a recent muon spin rotation and relaxation ͑SR͒ study 8 13 attempted to answer these questions based on bulk macroscopic measurements of Co͑Al 1−x Co x ͒ 2 O 4 system. They proposed that the spin-liquid state is realized in CoAl 2 O 4 ͑x =0͒, while with increasing Co substitution x the second-neighbor coupling J 2 decreases and collinear AFM long-range order develops.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Therefore, for our samples, especially W350, it is most likely that Co 3þ cations on the exposed surface planes in the O position of Co 3 O 4 nanostructures are reduced to Co 2þ cations by surface oxygen deficiency. The subsequent x-ray photoelectron spectroscopy (XPS) results (not shown here) further confirmed this hypothesis, and in addition, several groups of researchers 21,22 have found room temperature ferromagnetism in Co 3 O 4 and identified the original microscopic mechanism as due to Co 2þ ions replacing Co 3þ in the O positions by different methods. The XPS indicates that (1) the W350 sample is high purity, which can rule out impurity and metallic Co magnetic particle effects; and (2) W350 presents a higher amount of Co 2þ , which is caused by the Co 3þ -oxygen vacancy complex, since the satellite peak of Co 2p3/2 in W350 is higher than for the other samples.…”
Section: Resultssupporting
confidence: 59%
“…The next-nearest neighbor interactions are particularly important in Co-Al-O spinels; therefore they also might be responsible for the complex arrangement of the A-site spins. After original submission of our paper, Ikedo et al 42 reported on the µSR studies of Co 3 O 4 which were interpreted in terms of an incommensurate spin configuration. By analogy with the strongly frustrated MnSc 2 S 4 spinel 20 they attributed the incommensurate spin order in Co 3 O 4 to a structural transition due to a charge-and/or spin-state change of the Co ions.…”
Section: Discussionmentioning
confidence: 99%